Using RQA for evaluating heart rate patterns under controlled breathing - Ladeira, Guênia; Oliveira-Lopes, Luís Cláudio; Lima, Gabriela V. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, the variation of time and amplitude of the electrical stimulation of the heart muscle is analyzed during respiratory control exercise, effect of the autonomic nervous system. The specifics are verified by recurrence plot, and recurrence quantification analysis. The analysis revealed distinguished behavior of the electrical stimulation of the heart. And, the cross recurrence between the variations of amplitude and time demonstrated the equilibrium relationship in the cardiac cycles, which are accentuated in the exercise of concentration.